1993
DOI: 10.1111/j.1399-6576.1993.tb03714.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct vascular effect of ropivacaine in femoral artery and vein of the dog

Abstract: A study was conducted to examine the direct vascular effect of ropivacaine, in comparison with the effect of bupivacaine and lidocaine. Changes in tension induced by ropivacaine (10(-5)-3 x 10(-3) mol l-1) and lidocaine (10(-5)-10(-2) mol l-1) were examined cumulatively in vascular rings of dog femoral artery and vein under basal tension, or in those which had been precontracted with phenylephrine submaximally in Krebs' bicarbonate solution at 37 degrees C aerated with 95% O2 and 5% CO2 (pH 7.4). The change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
0
4

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 16 publications
(6 reference statements)
2
24
0
4
Order By: Relevance
“…There were no significant differences in the IOP levels between the groups, even though the IOP was decreased significantly below baseline values at 10 min in the ropivacaine group. It has been reported that the vasoconstrictive effect of ropivacaine leads to a decrease in the intraocular blood volume and that this might play a role in the observed decrease in the IOP (Nakamura et al 1993;Ishiyama et al 1997;Nociti et al 2001;Ozcan et al 2003). In addition, the IOP might have been decreased in the ropivacaine group because the diffusion of ropivacaine through the tissues may be faster than that of lidocaine.…”
Section: Discussionmentioning
confidence: 91%
“…There were no significant differences in the IOP levels between the groups, even though the IOP was decreased significantly below baseline values at 10 min in the ropivacaine group. It has been reported that the vasoconstrictive effect of ropivacaine leads to a decrease in the intraocular blood volume and that this might play a role in the observed decrease in the IOP (Nakamura et al 1993;Ishiyama et al 1997;Nociti et al 2001;Ozcan et al 2003). In addition, the IOP might have been decreased in the ropivacaine group because the diffusion of ropivacaine through the tissues may be faster than that of lidocaine.…”
Section: Discussionmentioning
confidence: 91%
“…[6][7][8][9] In contrast, local wound infiltration of ropivacaine results in a longer duration of action compared to bupivacaine, which has been attributed to a direct vasoconstrictive effect of ropivacaine on surrounding vessels. 10,11 In 2005, Yu et al 12 demonstrated the direct vasoconstrictive effect of ropivacaine on de-endothelialized rat aortic vasculature which Sung et al 3 reaffirm in this issue. Sung et al 3 demonstrated that clinically relevant concentrations of S-ropivacaine (Naropin TM ) at between 10 lM to 1 mM caused vasoconstriction of de-endothelialized rat aorta.…”
mentioning
confidence: 65%
“…Ces concentrations, quoique bien plus élevées que les seuils cardiotoxiques et neurotoxiques pour le SNC , se trouvaient à proximité des nerfs pendant des injections périphériques, neuraxiales ou locales de ropivacaïne. Les actions vasomotrices directes de la ropivacaïne ont été étudiées dans différentes structures vasculaires, notamment les capillaires, 10 les veines fémorales, 11 les artères ombilicales, 13 les artères fémo-rales, 11 et l'aorte. 12,14,15 Certaines études n'ont pas montré d'effet de la ropivacaïne sur la détérioration de la vasorelaxation, 15 alors que d'autres ont observé des effets vasoconstricteurs directs.…”
unclassified
See 1 more Smart Citation
“…Os resultados observados confirmam os obtidos por outros autores no que se refere às repercussões sobre as funções cardiovascular e neurológica, segundo os quais as duas drogas foram eficazes e não produziram alteração clínica significativa no sistema cardiovascular e neurológico 16 . No entanto, o estudo foi realizado em pacientes adultos e não foram dosadas as concentrações plasmáticas das duas drogas.…”
Section: Discussionunclassified